Teacher's Duties and Responsibilities - Riyanto, Muklis; Sayer, Inaad Mutlib (PPSDP International Journal of Education, 2022)
The purpose of this study was to obtain an overview of the duties and responsibilities of teachers. This study uses library research methods. The results show that the duties and responsibilities of teachers are professional duties, humanitarian tasks, and social tasks. The teacher's role in the teaching and learning process are the teacher's role in administration, the teacher's role as a person, and the teacher's role as a psychologist. Teacher responsibilities are professional, social, moral-spiritual, and personal.